Mendorong Pendidikan Kesehatan Reproduksi Remaja Di Bandar Lampung Melalui Dance Four Life - Rika Yuliana; Novita Tresiana; Dewi Brima Atika (Jurnal Administrativa, 2019)
The need for reproductive health education has become an issue that needs to be addressed at the national level. Reproductive health education will help adolescents to have positive values ​​in reproductive aspects as well as skills to protect themselves from various risks of reproductive and sexual diseases including the ability to fight for the rights of adolescents to live healthy lives. To continue to improve the reproductive health education of adolescents in Bandar Lampung, Perkumpulan Keluarga Berencana Indonesia (PKBI) of Lampung Province takes an important role in improving adolescent reproductive health education by implementing the Dance Four Life program (Dance4life). The purpose of this study was to obtain an analysis of the effectiveness of the Dance Four Life program (Dance4life) in improving adolescent reproductive health education in Bandar Lampung. This type of research is descriptive research with a qualitative approach. Thelocationof this research was conducted at PerkumpulanKeluargaBerencana Indonesia (PKBI) in Lampung Province.The results of this study indicate that the effectiveness of the Dance Four Life (Dance4life) program in improving adolescent reproductive health education in Bandar Lampung can be assessed based on Duncan's indicators of effectiveness in Steers (1985: 53), namely the achievement of goals and timeframes in the Dance Four Life program. (Dance4life); integration in the form of a socialization process carried out and procedures in the effectiveness of the Dance Four Life program (Dance4life); adaptation in the form of increasing capabilities and facilities and infrastructure that support the running of the program. Based on these indicators, the effectiveness of the Dance Four Life (Dance4life) program in improving adolescent reproductive health education in Bandar Lampung has been carried out effectively, although there are still obstacles, namely the indicators of timeframes that have not been efficient where the time provided by the school is not scheduled regularly.